'We're not hard-to-reach, they are!' Integrating local priorities in urban research in Northern England: An experimental method. Issue 1 (January 2018) - Symons, Jessica
In this article the author identifies the dichotomous nature of a government approach which insists on autonomy. Exhortations to communities to be independent while fostering dependent relations lead to a kind of paralysis that inhibits people's abilities to progress. These insights were gained in Salford, UK in a former working class community fatigued by government intervention. As part of an academic project focused on supporting local people's ideas, new ways of engaging were explored. However the researchers' role as project directors and the status of the university also had impacts on fostering self-determination. The author proposes that a reflexive strategy identifying and ameliorating the multiple points of government interventions in low-income communities would go far in nurturing people's productivity. This includes working with local intermediaries who have an intimate knowledge of the communities they serve.